“I will prove that ‘disabled’ is just a word”: Phenomenology, adaptive athletes and the adaptabilities model of disability - Schwartz, Norah Anita; von Glascoe, Christine Alysse (Social science & medicine (1982), 2025)
Involvement in adaptive athletics, including adaptive adventure sports, has been steadily increasing over the past few decades. With this growth, a new model of disability that addresses the intersection of athletics and impairment among bio-divergent athletes is called for. In this article, we use reflexive phenomenology to explore the active creation of social meaning among athletes with physical, developmental and neurological impairments. Five salient categories emerged from open-ended, in-depth interviews and immersed participant observation including: life interrupted, liminal spaces, post-traumatic growth/biographical renewal, mental fortitude, and living life aside from disability. Results demonstrate the transformative power of adaptive athletics and the concept of adaptability. Building upon the affirmative model of disability and the results of this study, we developed the ‘adaptabilities model of disability’, which rests upon a social values base of inclusion, diversity, accessibility, inclusivity, interdependence and leadership within the context of the adaptive athletic community. •Adaptive athletics includes anyone with a physical, learning or neurological impairment wishing to participate in sports.•Narratives provided by adaptive athletes portray transitions from life interrupted, liminality and biographical renewal.•Adaptive athletics has transformative power for adaptive athletes as well as for society.•The adaptabilities model accommodates challenges and abilities of biodivergent athletes.•The adaptabilities model is based on inclusion, equality, diversity, interdependence, leadership and community.